Perbanyakan Vegetatif Jambu Bol (Syzygium Malaccense) Melalui Teknik Sambung Pucuk - Adinda Munthe; Della Azzahra Batubara; Mawar Gultom; Nursakinah Harahap; Rani Simanjuntak; Syalsabila Pane; Aswarina Nasution (CV. Rayyan Dwi Bharata, 2026)
Guava (Syzygium malaccense) is a tropical fruit plant that has economic value and health benefits because it contains many active compounds that are good for the body. One way to vegetatively propagate guava is by using the grafting technique. This study aims to determine the process and success of the grafting technique on guava plants at the Horticultural Seed Development Unit of the Food Security, Agriculture, and Fisheries Service of Medan City and used a descriptive method through direct observation in the field. The selection of rootstock and scion, grafting procedures, binding the graft, and care of grafted seedlings are all part of the study. The results showed that the guava grafting technique was successful, with scion remaining fresh and new shoots emerging after the procedure. The accuracy of the cambium meeting between the rootstock and scion, the quality of the plant material, environmental conditions, and care after grafting are all factors that influence the success of grafting. Maintaining the superior traits of the parent plant, accelerating fruiting, producing uniform seedlings, and increasing plant resistance to environmental conditions, pests, and diseases are some of the advantages of this technique. Therefore, grafting can be an effective technique for producing superior guava seedlings.